Integrating the Readiness and Usability Models for Assessing the Information System Use - Yuniarto, Dwi; Esa, Firmansyah; A'ang, Subiyakto; Mulya, Suryadi; Dody, Herdiana; Aedah, Abd Rahman (2018)
In the systematic view, the use of information system (IS) can be separated into three main parts, i.e., the users as the actor of the use, the use itself as a process, and the system as the used object. However, most of the usability studies focus on the process and object points. The number of scholars who study about the actor of the use is still rare. This is an interesting phenomenon how to develop a comprehensive model which combining the three parts of the abovementioned parts of the systematic perspective. The purpose of this study was to understand the influential relationships between the readiness and usability factors towards the use of IS and to integrate the readiness and usability models in the context for assessing the use of a new IS. The proposed model was developed by adopting the Parasuraman’s readiness model and the Nielsen’s usability model, in terms of an inputprocess- output (IPO) logic. Besides the placement transparency of the ten variable within 25 influential relationships, the study also demonstrates coherently the definitions of the variables, its indicators, and the questions of each item measurements.